THE INFORMATION SUPPORT OF ORGANIZATION CAR TRAFFIC VOLUME IN THE FUNCTIONING OF THE SINGLE AUTOMATED CONTROL SYSTEM OF "UKRZALIZNYISIA" FREIGHT TRANSPORTATION - Papahov, O. Yu.; Okorokov, A. M.; Logvinov, O. M. (Science and Transport Progress, 2008)
The possible variants of change of order and technique of calculation of the plan of trains formation are considered with transition to the firm diagram of their traffic under condition of providing with the authentic information about the system state and the regulation of loading means.